Carbohydrate-Based Vaccines Methods and Protocols - Lepenies, Bernd.; Lepenies, Bernd. (Methods in Molecular Biology,, 2015)
This volume summarizes current cutting-edge methods related to carbohydrate-based vaccines, from the identification of a suitable carbohydrate antigen via the preparation of glycoconjugate vaccines to the characterization of vaccine candidates for their use in pre-clinical and clinical studies. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Carbohydrate-Based Vaccines: Methods and Protocols aims to be a valuable manual that will facilitate research in the field of carbohydrate-based vaccines.